SOME FACTORS RELATED TO ACADEMIC STRESS COPING STRATEGIES AMONG STUDENTS OF THE FACULTY OF FOREIGN LANGUAGES, THANG LONG UNIVERSITY, ACADEMIC YEAR 2021–2022 (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze several factors related to coping strategies for academic stress among students of the Faculty of Foreign Languages, Thang Long University, in the 2021–2022 academic year.Methods: A cross-sectional descriptive study was conducted on 452 students from the Faculty of Foreign Languages, Thang Long University.Results: Students majoring in English, with average or above-average economic conditions, living independently, not under academic pressure from family, and who had not repeated any courses in the previous semester were more likely to adopt approach coping strategies (p